Optimized routing for providing ethernet LAN services. - van Haalen, Ronald (IEEE Communications magazine)
Ethernet's-move into metropolitan and wide area networks is driving a rapidly growing market opportunity. Current Ethernet services come in two basic flavors, Ethernet line and LAN, providing point-to-point and multipoint connectivity, respectively. The LAN services, although more cost effective, are lagging behind in deployments due to associated QoS and bandwidth provisioning issues. The Ethernet service provider needs to provision the network to meet current and future traffic demands, where the traffic is unpredictable and bursty. The goal is to minimize. overprovisioning and complexity. To add to the challenge, Ethernet routing is based on simple self-learning and relies on spanning tree routing. In this article we propose an Ethernet-specific load balanced routing mechanism, which is robust to dynamic traffic demand. It significantly reduces overprovisioning, is simple and static, and requires only bandwidth profiles associated with service level agreements at the ingress and egress links. Our simulation results show that our scheme provides performance improvements over a recently proposed approach for switched Ethernet as well as a related load balancing approach for Ethernet over MPLS networks.